APLIKASI IRIGASI TETES “RO DRIP” PADA LAHAN KERING - -, Yusriadi; -, Harsani (Jurnal Ilmiah Ecosystem, 2020)
Drip irrigation application is an irrigation system using a drip hose, which aims to make water use effective. Drip irrigation is not a new technology, but has long been developed especially on agricultural land that lacks water resources. Insufficient water sources on agricultural land, so farmers must rely on pumping systems from the nearest water source. With a direct pumping system will increase production costs. For one-time irrigation directly using pumping, farmers need at least 12 liters of fuel oil / day / ha. In other words, farmers must incur additional costs for irrigation purposes. Whereas for the time brackets of horticultural plants, it takes approximately three months for the plants to produce. If farmers have to irrigate land 3 to 4 times per month, farmers need 36 liters of fuel oil per month / ha. Assuming the price of premium fuel oil is Rp 6,650 / liter, then the farmer must at least pay an additional fee of Rp. 239,400 / month / ha. Therefore, the application of "RO DRIP" drip irrigation on dry land is expected to be able to reduce production costs for farmers. Application of drip irrigation is expected to be able to maximize the use of water so that farmers' production activities are more effective and efficient. Drip irrigation is very easy to apply because the materials and equipment used are very simple and easy to obtain. The advantages of this irrigation system are that the use of water will be controlled, the watering schedule can be arranged, the water needs for each plant can be met, and the provision of fertilizer can be directly through the reservoir. So that this irrigation system can simplify and save production costs for farmers.